An Analysis on the Association Between ABO and Rh Blood Groups with Obesity - (:unkn) unknown (Springer, 2019)
Overweight or obesity is a global and severe healthcare problem associated with many diseases. The rapid increase in the incidence of obesity all over the world devoted the researchers to analyze the parameters associated with obesity and overweight. The aim of the present study was to detect whether any connection exists between the ABO and Rh blood groups and obesity through statistical methods. Body length and body weight measurements of 306 female participants who referred to Sports Physiology and Blood Bank departments of Pendik Training and Research Hospital within Marmara University were obtained. Blood samples were also collected from each participant, and body mass index [BMI], ABO blood group and Rh blood groups were detected. The association of obesity with blood group and Rh blood group types was analyzed by statistical methods. Age, body weight, BMI, fat percentage, fat weight and muscle weight parameters of the participants were found statistically significant. In the logistic regression analysis conducted to detect the effect of ABO and Rh blood groups on obesity, a statistically significant association was found between ABO blood groups and obesity whereas a considerable association was also detected between Rh blood group and obesity. The authors found that the highest rate of the obese individuals was in A and Rh positive blood groups. © 2018, The National Academy of Sciences, India.
Keywords: ABO blood groups; Body mass index [BMI]; Obesity; Rh blood group